Making in schools: student learning through an e-textiles curriculum. Issue 5 (2nd September 2020) - Hébert, Cristyne; Jenson, Jennifer
ABSTRACT: Making and maker spaces have attracted increasing attention as potential sites for supporting K-12 student learning in science, technology, engineering, and mathematics (STEM) and as a means of competency development for computational and design thinking as well as technological literacy. While interest in making and maker spaces is high, little empirical research has been conducted that evaluates student learning through making in K-12 classroom spaces. In this study, we address this gap examining student learning through a making project: the construction of e-textiles, in this case, wearable hats, in a unit delivered in both a series of after-school workshops and as in-class lessons in a school in Ontario, Canada. Results demonstrated that students increased their understandings of coding and circuitry through making.